Network competition with heterogeneous calling patterns - Dessein, Wouter (online, 2000)
Abstract:
urn:nbn:de:0168-ssoar-116283
Keywords: (stw)Telekommunikation; (stw)Preiswettbewerb; (stw)Preismanagement; (stw)Markteintritt; (stw)Nachfrage; (stw)Kapazitätsplanung; (stw)Netzregulierung; (stw)Theorie; (stw)Telekommunikationsnetz; (thesoz)Telefon; (thesoz)Telekommunikation; (thesoz)ökonomisches Modell; (thesoz)Preispolitik; (thesoz)Preisbildung; (thesoz)Markterschließung; (thesoz)Wettbewerb; (thesoz)Nachfrage; Arbeitspapier; Graue Literatur; Buch; Online-Publikation; Als Aufsatz endgültig erschienen; Telekommunikation; Fernmeldewesen; Telekommunikationswirtschaft; Preiswettbewerb; Preispolitik; Markteintrittsstrategie; Nachfrage; Kapazitätsplanung; Netzzugang; Theorie; ISDN; Telekommunikationsnetz